Chromosomal Anomalies in Acute Myeloid Leukemia: Cytogenetic Results of -417 Cases Froma Single Center - Nüket Yürür-Kutlay; Timur Tuncalı; Halil Gürhan Karabulut; Faika Sadeghi; İbrahim Akalın; Burcu Sağlam; Hatice Ilgın Ruhi; Arzu Vicdan; Ajlan Tükün (Ankara Üniversitesi Tıp Fakültesi Mecmuas)

(untitled)
Aim: Cytogenetic markers have important roles in the diagnosis and follow up of leukemia patients. In AML patients cytogenetic results are relatively more complicated compared to other leukemias. Over 150 recurrent numerical and structural chromosomal changes have been reported in AML. Evaluation of cytogenetic analysis results of large patient series will help the genetic knowledge about AML formation to accumulate and also to define novel prognostic or diagnostic markers.